2003
DOI: 10.1046/j.1440-1754.2003.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal cortical tumours: 25 years’ experience at the Royal Children's Hospital, Melbourne

Abstract: Adrenal cortical tumours should always be considered in the differential for adrenal hormone excess. New information provided by mutational analysis may predict ongoing risks. Lifelong regular follow up is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…Although not the topic of this guideline, all children with a diagnosis of ACC should undergo a systematic search of germline TP53 pathogenic variants, because 50-90% of ACC in children are related to germline pathogenic TP53 variants (293,294,295).…”
Section: Reasoningmentioning
confidence: 99%
“…Although not the topic of this guideline, all children with a diagnosis of ACC should undergo a systematic search of germline TP53 pathogenic variants, because 50-90% of ACC in children are related to germline pathogenic TP53 variants (293,294,295).…”
Section: Reasoningmentioning
confidence: 99%
“…In contrast, Michalkiewicz et al (10) reviewed the cases of 20 patients with small adrenocortical tumors recorded in the International Registry of Childhood Adrenocortical Tumors between May 1988 and December 1994; all of these patients had clinical signs of virilization, 7 had signs or symptoms of Cushing syndrome, and no feminizing features were observed. In another study conducted at the Royal Children's Hospital in Melbourne, there were 12 children with adrenocortical tumors over a 25-year period, none of which had symptoms of feminization (11).…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding ACT during childhood is scarce; however, it was stated that in childhood, the most prevalent form is virilizing ACT (10,11,12,13,14,15,16). Michalkiewickz et al (13) investigated the data of 254 children with ACT from an international registry and suggested that 55.1% of children with ACT had a tumor leading to isolated virilization and 29.2% had a tumor leading to combined virilization and Cushing’s syndrome.…”
Section: Discussionmentioning
confidence: 99%